Incidence and cost of hypoglycemic events requiring medical assistance in a hospital setting in Denmark. (May 2016) - Lyngsie, Pavika J; Lopes, Sandra; Olsen, Jens
Aims: The purpose of this study was to estimate the incidence and hospital costs associated with hypoglycemic episodes (HEs) requiring hospital admission or emergency room (ER) visits in Denmark.Materials & methods: This study analyzed data from the National Patient Registry. Data on HE-related hospital admissions or ER visits occurring between 2008 and 2011 were collected and analyzed.Results: There were 1906 hospital admissions and 803 ER visits in 2008 compared with 1646 hospital admissions and 547 ER visits in 2011, corresponding to a decrease in incidence from 10.6 to 7.1. The estimated annual total hospital costs ranged from €3.0 million in 2008 to €2.3 million in 2011.Conclusion: HEs represent a major burden for the Danish healthcare system.